Sex Differences in Post-exercise Hypotension, Ambulatory Blood Pressure Variability, and Endothelial Function After a Power Training Session in Older Adults - de Oliveira Carpes, Leandro; Domingues, Lucas Betti; Schimitt, Renato; Fuchs, Sandra C.; Alhalimi, Taha; Tanaka, Hirofumi; Ferrari, Rodrigo (Frontiers in Physiology, 2021)
Background: The efficacy of power training (PT) to acutely reduce blood pressure (BP) in participants with hypertension is controversial and no studies have assessed the influence of sex on post-exercise hypotension and its mechanisms in older adults. Purpose: The aims of this secondary, exploratory analysis were to compare the effects of a single bout of PT on post-exercise hypotension, BP variability, and endothelial function between older men and women with hypertension. Methods: Twenty-four participants with hypertension (12 men and 12 women aged to >60 years old) took part in this crossover study and randomly performed two experimental sessions: power exercise training (PT) and non-exercising control session (Con). The PT protocol was composed of 3 sets of 8-10 repetitions of five exercises performed in the following order: leg press, bench press, knee extension, upright row, and knee flexion, using an intensity corresponding to 50% of one repetition maximal test (1RM) and 2 min intervals between sets and exercises. The concentric phase of exercises during each repetition was performed "as fast as possible" while the eccentric phase lasted 1 to 2 seconds. During Con, the participants remained at seated rest on the same exercise machines, but without any exercise. Each protocol lasted 40 min. Office BP, Flow-mediated dilatation (FMD), 24-hour ambulatory BP, and the average real variability (ARV) of systolic and diastolic BP were assessed before and after experimental sessions. Results: Comparing men and women, a reduced systolic BP (Post 60': -15 mmHg, P=0.048; Average post 1 hour: -7 mmHg, P=0.046) and diastolic BP (Post 60': -9 mmHg, P=0.049) after the first hour of PT were found in men. In relation to 24-hour ambulatory BP, ARV and FMD, no statistically significant differences were found between men and women. Conclusion: In older adults with hypertension, the office BP response after the experimental sessions was different in men and women, showing that the PT protocol is more effective to acutely reduce BP in men. Additionally, the mechanisms behind this reduction remain unclear. This finding suggests that sex/gender cannot be combined to analyze post-exercise hypotension.